The fertility of buck semen after A 11 year storage in liquid nitrogen ( 192°C) - ΣΑΜΟΥΗΛΙΔΗΣ Σ.; ΦΟΥΚΟΣ Α.; ΤΣΑΚΑΛΩΦ Π. (Journal of the Hellenic Veterinary Medical Society, 2019)
A total of 30 goats were inseminated with frozen buck semen that had been stored for a period of 11 years. Of these goats, 16 conceived on the first (52,33%) and 4 on the second insemination (28,57%), i.e. a total of 20 animals (66,66%) conceived and kidded as follows: 9 animals had singles, while the remaining 11 had twins, i.e. a total of 31 kids were born. The number of the male kids amounted to 26(83,87%) and that of the female kids to 5(16,13%). Inseminations with the same batch of frozen buck semen carried out soon after freezing, i.e. 11 years previously, had the following results: a total of 54 goats were inseminated, of which 38 animals (70,37%) conceived and kidded. It is concluded that the fertility of frozen buck semen after a period of storage of 11 years declined by 3,71%. This difference in conception rate was statistically insignificant